Typology of Islamic Movements in Indonesia 18-19 Century - Toipah, Toipah; Fiza, M. Syakir Ni'amillah (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2023)
The study explores the typology of the Islamic movement in Indonesia in the 18th to 19th centuries with a focus on resistance to Dutch colonialism, education, as well as tasawuf and tarekat aspects. The phenomenon of religious revivalism, especially in the growth of the practitioners and tarekat, was closely linked to the rise of the people of Hajj in the 19th century. Dutch colonial politics, in its attempt to humanize Indonesia from Islam, used Western education as its primary tool. The process of secularization occurs as a result of the penetration of Western influence into the education system, forming secular groups that tend to support non-religious organizations. The emergence of the Islamic modernist movement as a result of the diversification of the movement, especially in the fields of law, leadership, and conflict between custom and religion. Political developments show the accommodation and polarization between the traditionalist and modernist groups, shaping the diversity of Islamic movement in Indonesia. The study uses a library method with a qualitative approach, analysing contemporary historical sources related to the Islamic movement in Indonesia during that period. The results identified the typology of the movement based on its patterns and characteristics, including political, economic, educational, tasawuf, and tarekat. Various events of resistance to colonialism are described, such as the Padri Movement (1819-1837) in Minangkabau, the Diponegoro War (1825-1839) in Java, the Banjarmasin War, and the rebellion in Banten influenced by the Qadiriyah tarekat wal Naqsyabandiyah. Educational institutions, especially gymnastics, have become the focus of the Islamic movement. The importance of the role of tasawuf and tarekat in motivating resistance against colonial oppression is illustrated, for example, through the network of tarekat Syatariyah in the Java War. In conclusion, the Islamic movement in Indonesia in the 18th to 19th centuries involved complex typologies, covering aspects of resistance, education, and spirituality, shaping the dynamics of Indonesian Islamic history.